Utility of proactive infliximab levels in paediatric Crohn's disease. Issue 3 (27th June 2018) - Burgess, Christopher J; Reilly, Claire; Steward-Harrison, Lana; Balouch, Fariha; Lewindon, Peter J
Abstract : Objective: Infliximab (IFX) has an established role in Crohn's disease (CD), with serum trough levels of IFX (TLI) increasingly used to optimise dosing. We report the utility of routine, proactive TLI in children on combination therapy with immunosuppression (IS) from a single paediatric centre. Methods: This is a retrospective chart review of all children with CD receiving IFX therapy conducted betweenJanuary 2014–May 2017. Clinical phenotype, duration of therapy, TLI (µg/mL), drug antibodies, type of IS, biomarkers and changes in management were recorded. Results: 60 children (8–17 years; median 14.1 years) had 206 TLIs recorded. 56/60 (93%) were on IS, with 5/60 (8%) developing antidrug antibodies (ADAs). 63/206 TLIs were recorded duringan episode of relapse (median 3.0 µg/mL) vs 143/206 TLIs recorded in remission (median 5.2 µg/mL). For children with TLI <3 µg/mL, 31/63 (49%) were in relapse vs 30/143 (21%) in remission. For children with TLI >7 µg/mL, 7/63 (11%) were in relapse vs 46/143 (32%) in remission. Change in management resulted from 43/206 (21%) TLIs in 31/60 (52%) children: 21 dose escalations, 12 de-escalations and 10 changed to adalimumab. Of 31 postinduction TLIs, 15/17 (88%) children with TLI >7 µg/mL achieved clinical and biochemical remission for the duration of therapy (median 14 months), while 4/5 (80%) children with TLI <3 µg/mL required early dose escalation. Combination therapy with thiopurines (TP) (median TLI 4.9 µg/mL) versus methotrexate (MTX) (median TLI 5.2 µg/mL) achieved comparable levels with no difference in relapse frequency. Conclusions: Routine, proactive TLIs guide optimal management in children with CD. Postinduction and during maintenance, levels <3 µg/mL were associated with relapse and levels >7 µg/mL with sustained remission. Combination IS with TP and MTX appears to offer comparable TLI and ADA rates.